1 - Governing Gender: Violent Extremism in Northern Nigeria - Okech, Awino (Africa Development, 2021)
This article draws on a qualitative study piloted in Maiduguri, Northern Nigeria, to unpack the gender logics that shape why women join Boko Haram, their roles, how they are perceived by their communities on their return and how these dynamics inform the ‘deradicalisation’ programmes of the Nigerian government and civil society organisations. The study reveals that the absence of a gender power analysis reproduces the dominant tropes evident in radicalisation theories and programmes about who is radicalised and why, thus limiting a holistic response to the factors that drive association with Boko Haram in Northern Nigeria. The article points to the opportunities that a more nuanced reading of women’s experiences of associating with armed groups and their return to their communities offers to re-conceptualising integration programmes.